Design of a circular polarization microstrip antenna at 2.4Ghz - Harith, Zuraidah (2005)
Microstrip patch antennas represent one family of compact antennas that offer a conformal nature and the capability of ready integration with communication system’s printed circuitry. In this project, a 2.4 GHz circular polarization microstrip antenna is designed, constructed and measured. The microstrip antenna chose is a dual –fed circular polarized microstrip antenna. The antenna consists of rectangular patch and 3 dB hybrid. The dual – fed circular polarized microstrip antenna is etched on a FR4 with dielectric substrate of 4.5 with the height of 1.6 mm. Circular polarization is obtained when two orthogonal modes are equally excited with 90° phase difference between them. Circular polarization is important because regardless of the receiver orientation, it will always able receiving a component of the signal. This is due to the resulting wave having an angular variation.